Lasers in the conservation of artworks VIII : proceedings of the International Conference on Lasers in the Conservation of Artworks VIII (LACONA VIII), 21-25 September 2009, Sibiu, Romania /: proceedings of the International Conference on Lasers in the Conservation of Artworks VIII (LACONA VIII), 21-25 September 2009, Sibiu, Romania. (©2011) - Unknown
No abstract available